Allotopic expression of mitochondrial genes: Basic strategy and progress - I. Made Artika (Genes and Diseases, 2020)
Allotopic expression of mitochondrial genes is a deliberate functional relocation of mitochondrial genes into the nucleus followed by import of the gene-encoded polypeptide from the cytoplasm into the mitochondria. For successful allotopic expression of a mitochondrial gene, several key aspects must be considered. These include the different codon dictionary used by the mitochondrial and nuclear genomes, different codon preferences between mitochondrial and nuclear-cytosolic translation systems, and the provision of an import signal to ensure that the newly translated protein in the cytosol is successfully imported into mitochondria. The allotopic expression strategy was first developed in yeast, a useful model organism for studying human and other eukaryotic cells. Currently, a number of mitochondrial genes have been successfully recoded and nuclearly expressed in yeast and human cells. In addition to its use in evolutionary and molecular biology studies, the allotopic expression strategy has been developed as a potential approach to treat mitochondrial genetic disorders. Substantial progress has been recently achieved, and the development of this technique for therapy of the mitochondrial disease Leber's hereditary optic neuropathy (LHON) has entered phase III clinical trials. However, a number of challenges remain to be overcome to accelerate the successful application of this technique. These include improvement of nuclear gene expression, import into mitochondria, processing, and functional integration of the allotopically expressed polypeptides into mitochondrial protein complexes. This review discusses the current basic strategy, progress, challenges, and prospects of the allotopic expression strategy for mitochondrial genes.